The chromatin remodelers RSC and ISW1 display functional and chromatin-based promoter antagonism - Timothy J Parnell; Alisha Schlichter; Boris G Wilson; Bradley R Cairns (eLife, 2015)
ISWI family chromatin remodelers typically organize nucleosome arrays, while SWI/SNF family remodelers (RSC) typically disorganize and eject nucleosomes, implying an antagonism that is largely unexplored in vivo. Here, we describe two independent genetic screens for rsc suppressors that yielded mutations in the promoter-focused ISW1a complex or mutations in the ‘basic patch’ of histone H4 (an epitope that regulates ISWI activity), strongly supporting RSC-ISW1a antagonism in vivo. RSC and ISW1a largely co-localize, and genomic nucleosome studies using rsc isw1 mutant combinations revealed opposing functions: promoters classified with a nucleosome-deficient region (NDR) gain nucleosome occupancy in rsc mutants, but this gain is attenuated in rsc isw1 double mutants. Furthermore, promoters lacking NDRs have the highest occupancy of both remodelers, consistent with regulation by nucleosome occupancy, and decreased transcription in rsc mutants. Taken together, we provide the first genetic and genomic evidence for RSC-ISW1a antagonism and reveal different mechanisms at two different promoter architectures.